1997
DOI: 10.1007/s004240050493
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell-mediated induction of ICAM-1, VCAM-1 and E-selectin in endothelial cells in vitro: constitutive release of inducing mediators but no effect of degranulation

Abstract: Mast cell (MC)-mediated induction of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) and of E-selectin was studied in cultures of rat heart endothelial cells (EC) and human umbilical vein EC (HUVEC) respectively. MC induced VCAM-1 and E-selectin, but hardly any ICAM-1 in EC. Induction was not dependent on MC degranulation, but seemed to be provoked by constitutively released substances, other than histamine, from MC. Co-incubation of MC and EC, allowing for direct cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…These pro-inf lammator y mediator and vasoactive substances attack vessels from outside [40] , promote the expression of VCAM-1 and E-selectin on endothelial cells [41] , increase the rolling and adhesion of leukocytes, and enhance the albumin leakage [39,41,42] . In the present study, the degranulation of mast cells induced by LPS infusion was found to be markedly inhibited by the treatment with compound Danshen injection in terms of the degranulated mast cell ratio, sug gesting that compound Danshen injection is also capable of protecting the microvessels by blockage of vasoactive substances from outside.…”
Section: Discussionmentioning
confidence: 99%
“…These pro-inf lammator y mediator and vasoactive substances attack vessels from outside [40] , promote the expression of VCAM-1 and E-selectin on endothelial cells [41] , increase the rolling and adhesion of leukocytes, and enhance the albumin leakage [39,41,42] . In the present study, the degranulation of mast cells induced by LPS infusion was found to be markedly inhibited by the treatment with compound Danshen injection in terms of the degranulated mast cell ratio, sug gesting that compound Danshen injection is also capable of protecting the microvessels by blockage of vasoactive substances from outside.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse TNF‐α appears to be released from MC upon transcription, but also from cytoplasmatic stores, 17 the latter having a major impact on the leucocyte recruitment activity in experimental inflammation 18 . In addition, recent data suggest that the release of rat MC‐prestored mediators (possibly histamine and TNF‐α) hardly has any effect on ICAM‐1 expression upon activation 19 …”
Section: Introductionmentioning
confidence: 99%
“…When degranulated, mast cells release histamine and TNF-α, and initiate the cytokine cascade, which leads to the expression of vascular cell adhesion molecule-1 (VCAM-1) and E-selectin on endothelial cells and subsequent neutrophil-induced injury (Frangogiannis et al, 1998;van Haaster et al, 1997). The inhibitory effect of PNS on mast cell degranulation was previously identified from the results of experiments with the compound Myakuryu .…”
Section: Discussionmentioning
confidence: 87%